Community media's role in changing centre‐periphery relations through participatory, not-for-profit journalism. (1st June 2021) - Doliwa, Urszula; Purkarthofer, Judith
Traditional notions of journalism focus exclusively on professionals, often embedded in media outlets and publishing houses. However, preceding decades have seen transformations in the understanding of journalism. This contribution sets out to explore the role of community media in working towards the recognition of participatory, not-for-profit journalism, more diverse discourses and enhanced participation, especially in relation to minorities. This research draws on policy documents at the European level, reports from European projects with community media involvement as well as on interviews with community media activists and journalists. As a result, we can show strategies of bringing peripheral actors to the centre by using community media based on access and participation, social inclusion, giving a voice and media literacy development. The study proposes a model of the role of community media in shifting peripheral actors to more central positions.